DETERMINATION OF SURFACE ENERGY AT THE INTERFACE BETWEEN POLYMER AND AGGRESSIVE AREA (World Science, 2025)
There are discussed the methodology and results of the study of surface energy at the interface between a polymer and an aggressive area.There are presented the methods and results of x-ray diffraction studies of intermediate grain sires and apps on polymer surface.